2018
DOI: 10.1371/journal.pone.0190560
|View full text |Cite
|
Sign up to set email alerts
|

Is intuition really cooperative? Improved tests support the social heuristics hypothesis

Abstract: Understanding human cooperation is a major scientific challenge. While cooperation is typically explained with reference to individual preferences, a recent cognitive process view hypothesized that cooperation is regulated by socially acquired heuristics. Evidence for the social heuristics hypothesis rests on experiments showing that time-pressure promotes cooperation, a result that can be interpreted as demonstrating that intuition promotes cooperation. This interpretation, however, is highly contested becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 48 publications
6
50
0
Order By: Relevance
“…In sum, our results support the conclusion of Capraro (2017) that time pressure increases honesty in the deception game studied here. This observation is in line with other work where participants can take actions which help or harm others, namely economic cooperation games (Everett et al 2017;Isler et al 2018;Rand 2016). We conclude by suggesting that the Social Heuristic Hypothesis (Bear & Rand, 2016;Peysakhovich & Rand 2016;Rand et al 2014Rand et al , 2016, whereby typically advantageous behaviors are internalized as intuitive defaults, may help explain why -and when -honesty is intuitive versus deliberative.…”
Section: Discussionsupporting
confidence: 90%
“…In sum, our results support the conclusion of Capraro (2017) that time pressure increases honesty in the deception game studied here. This observation is in line with other work where participants can take actions which help or harm others, namely economic cooperation games (Everett et al 2017;Isler et al 2018;Rand 2016). We conclude by suggesting that the Social Heuristic Hypothesis (Bear & Rand, 2016;Peysakhovich & Rand 2016;Rand et al 2014Rand et al , 2016, whereby typically advantageous behaviors are internalized as intuitive defaults, may help explain why -and when -honesty is intuitive versus deliberative.…”
Section: Discussionsupporting
confidence: 90%
“…In sum, our results support the conclusion of Capraro (2017a) that time pressure increases honesty in the sender-receiver game studied here. This observation is in line with other work where participants can take actions which help or harm others, namely economic cooperation games (Everett et al 2017;Isler et al 2018;Rand 2016). We conclude by suggesting that the Social Heuristic Hypothesis (Bear & Rand, 2016;Peysakhovich & Rand 2016;Rand et al 2014Rand et al , 2016, whereby typically advantageous behaviors are internalized as intuitive defaults, may help explain why -and when -honesty is intuitive versus deliberative.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, they also found that the same effect is present in the prisoner's dilemma played in a loss frame. A similar warm-up procedure was followed by Isler, Maule and Starmer (2018), who also found that time pressure increases cooperation. Some works have explored the role of potential moderators.…”
Section: Review Of the Empirical Evidencementioning
confidence: 92%